"La conectividad en la red lógica y su incidencia en la gestión por procesos de la Universidad Técnica Estatal de Quevedo. 2013. "Implementación de redes LAN virtuales - Carreño Sandoya, Stalin Daniel (2015)
The University of Quevedo, issued the Statute Organizational Process Management, the same that is approved in second and final instance on January 24, 2012, once the Ministry of Labour Relations dated August 16, 2011 issued by the report favorable to its application. Given this change in organizational structure, was convenient to administer the data network so that fits these changes without affecting performance and is transparent to the end user, in the benefits of the institution it is that it has a structure robust communications both active and passive part which allowed for a logical structure that is adjusted to the organizational structure processes. Virtual networks (VLAN) for each sector and for each service in the field of networks were implemented, so that virtual networks for the administrative part, academic, computer labs and wireless networks were created, this organization ago easier to carry out the administration of the network and to add services without affecting its performance. For Internet access each VLAN servers using XenCenter as Gateway platform ClearOS operating system that allowed it to manage Internet service and establishing securities in each virtual network is virtualized.